Analisis Fouling Resin dan Efektivitas Regenerasi Kimia pada Unit Mixed Bed Demin Plant - Muhammad Genta Zuan Nur Illyasa; Sinardi (Journal of Research and Education Chemistry, 2026)
Analysis of Resin Fouling and Chemical Regeneration Effectiveness in Mixed Bed Demineralization Units. Water requirements for various activities, such as Steam Power Plants, require water quality in the form of mineral-free water (demineralized water) obtained through a demineralization process using a mixed bed. Along with frequent use, the resin will reach saturation due to the accumulation of contaminants (fouling) bound by the resin, which leads to a decrease in water quality. This research aims to identify the type of fouling in resin based on water quality and visual observation of the resin, as well as to analyze the effectiveness of chemical regeneration. The research methods used were water quality analysis and visual observation of the resin. Furthermore, the chemical regeneration process used an acid-base method (HCl and NaOH). The results showed that the water quality had average values for silica, total hardness, and conductivity of 16.71 ppb, 0 ppb, and 0.159 µS/cm, respectively, with a removal efficiency of 98.32%, 100%, and 96.79%. However, the final test showed silica values exceeding the standard of < 20 ppb. This indicates silica leakage in the outlet water. Furthermore, the color change from white to pink indicates fouling in the anion resin. The chemical regeneration results showed an effectiveness percentage of 67.43% for silica values and 35.22% for conductivity, bringing the water quality back into compliance with the standards. It can be concluded that the chemical regeneration process with NaOH and HCl is able to restore the resin's ability to improve water quality.